REBUILDING SOCIALISM: NOSTALGIA AND POLITICS IN ONLINE VIDEOGAME COMMUNITIES - Ferrer-Sheehy, Shane (AoIR Selected Papers of Internet Research, 2020)
Nearly 30 years on from the collapse of the Soviet Union and the Eastern Bloc, an entire cottage industry has arisen for the manufacturing and commodification of post-socialist nostalgia. While a lot of the more visible sites for this nostalgia are in physical spaces like museums, there are also equivalent spaces cropping up online. One such site of nostalgia is the online community surrounding the Slovak video game Workers and Resources: Soviet Republic (2019). A city builder set in a fictional Eastern Bloc country during the cold war, the game allows players to build and manage Soviet style cityscapes. But online discussions surrounding the game show that players are fans are interested in more than just game mechanics. Fan forums are filled with posts discussing the historical period simulated by the game, often in very personal terms. Some of these discussions take an overtly political tone, with participants debating the merits of socialist economic structures and civic institutions. Others are more directly personal, recalling the everyday lives of family members and occasionally childhood memories themselves. For these players, the video game seems to be more than just a hobby. It is a window into a past that only some of them have first hand experience with. Taking a qualitative approach by analyzing materials posted by the online fan community surrounding the video game Workers and Resources: Soviet Republic, this project seeks to explore the question of how red nostalgia is practiced in an online space.